Self-Assembly Engineering Nanodrugs Composed of Paclitaxel and Curcumin for the Combined Treatment of Triple Negative Breast Cancer - Zuo, Shuting; Wang, Zhenyu; An, Xianquan; Wang, Jing; Zheng, Xiao; Shao, Dan; Zhang, Yan (Frontiers in Bioengineering and Biotechnology, 2021)
The clinical outcomes of triple-negative breast cancer (TNBC) chemotherapy are unsatisfactory. Water solubility and biosafety of chemo drugs are also major barriers for achieving satisfactory treatment effect. In this study, we have reported a combinational strategy by self-assembly engineering nanodrugs PC NDs, which were composed of paclitaxel (PTX) and curcumin (Cur), for effective and safe TNBC chemotherapy. PC NDs were prepared through reprecipitation method without using any additional carriers. The PC NDs were preferentially taken up by TNBC cells and we also observed pH-related drug release. The cytotoxicity assay revealed that the PC NDs had a greater effect on TNBC cells than free PTX. Compared with free PTX and simple PTX/Cur mixture, PC NDs have shown higher therapeutic efficiency without obvious systemic toxicity. Therefore, the self-assembly engineered PC NDs might be a promising nanodrugs for efficient and safe TNBC chemotherapy.